Effects of Aerobic Exercises on Cardiovascular Endurance of Female Student Athletes - Muhammed Erano Debiso; Yonas Mebrat Dagnaw; Abinet Ayalew Wolde; Eyasu Merhatsidk Gebreegziabher (Indonesian Journal of Sport Management, 2025)
This study was aimed to investigating the effects of selected Aerobic exercises on improving cardiovascular endurance female student athletes at Ansho secondary and preparatory school. To achieve the raised objective, the researcher selected 48 female athletes. They were assigned in to experimental and control group purposively. The proper experimental data was collected for three consecutive months through careful follow up of the researcher. Control group female student athletes did not participate in any aerobic exercise. The data was properly analyzed using t-test, ANOVA, mean analysis and graphical statistical approaches. In experimental group the study assessed the effects of selected aerobic exercises on cardiovascular endurance among female student athletes using the Step-Up Test and the Twelve-Minute Run (TMR). In the Step-Up Test, the participants’ mean heart rate showed a consistent decrease across testing periods, indicating improved cardiovascular efficiency. Their pre-test mean value was 148.25 ± 5.70, which decreased to 135.5 ± 8.20 during the exercise period, and further declined to 122 ± 9.36 in the post-test. Similarly, performance in the Twelve-Minute Run demonstrated progressive improvement. The athletes covered a mean distance of 2621.17 ± 116.78 m during the pre-test, which increased to 2763.38 ± 131.51 m during training and reached 2868.98 ± 126.34 m in the post-test. Overall, the results show that participation in structured aerobic exercise led to significant improvements in cardiovascular endurance among the female athletes. The t-test analysis has confirmed that there were significant mean cardiovascular endurance difference between control and experimental group female student athlete on both twelve minute run and step test.  However, soon after they started their aerobic exercise the test has shown significant variation between the groups. Having deep statistical analysis, it was concluded that aerobic exercise had significant effect on cardio vascular endurance of the female student athletes in experimental group. Thus, school principals, Woreda sport and youth affairs department office and other stock holders should have to participate in motivating female students for aerobic exercise and they should also facilitate materials for schools and for the society as whole.